THE CORRELATION BETWEEN MASTERING VOCABULARY AND SPEAKING ABILITY (CASE STUDY AT SMA 10 FAJAR HARAPAN BANDA ACEH) - Rahmi Fhonna (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2014)
This research is about the correlation between mastering vocabulary and speaking ability, which is conducted in SMA Negeri 10 Fajar Harapan Banda Aceh. This study has 2 (two) objectives; to find out the correlation between students’ vocabulary mastery and their speaking ability as well as to find out the students achievement in mastering vocabulary and speaking ability. 48 students have been taken as sample of this study. The data is collected through observation and tests; vocabulary test and speaking test, then they are calculated by using the coefficient correlation Pearson product moment formula. With significant level α = 0, 05, the result of the test shows that there is positive correlation between mastering vocabulary and speaking ability with correlation value 0, 93. Since the score is high, it can be concluded, therefore, that the students’ vocabulary mastery has high correlation with their speaking ability.